2004
DOI: 10.1080/01674820400017830
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the ups and downs of pregnancy stress

Abstract: Despite substantial interest in the effects of stress on pregnancy, few instruments are available to measure pregnancy-specific stressors. Moreover, research has typically focused on the distressing, negative aspects of pregnancy. This report examines the reliability and validity of the Pregnancy Experience Scale (PES), a 41-item scale that measures pregnancy-specific daily hassles and uplifts. The PES was administered to two cohorts of low risk women at 24, 30, and 36 weeks (n = 52) or 32 and 38 weeks (n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 61 publications
3
138
0
2
Order By: Relevance
“…Pregnancy-related daily hassles were measured using a Dutch translation of the Pregnancy Experience Scale (PES; DiPietro, Ghera, Costigan, & Hawkins, 2004), consisting of 43 items (a ¼ .87). Example items are "discussing baby names with your spouse", and "preparing the nursery".…”
Section: Pregnancy-related Daily Hasslesmentioning
confidence: 99%
“…Pregnancy-related daily hassles were measured using a Dutch translation of the Pregnancy Experience Scale (PES; DiPietro, Ghera, Costigan, & Hawkins, 2004), consisting of 43 items (a ¼ .87). Example items are "discussing baby names with your spouse", and "preparing the nursery".…”
Section: Pregnancy-related Daily Hasslesmentioning
confidence: 99%
“…Two shortcomings limit the interpretation of the pregnancy stress variable as a measure of maternal stress. Although multiple domains -from the occurrence of life events, 31 to pregnancy-specific daily events, 46 to the experience of racism 47,48 -are expected to contribute to overall stress, data to assess the influence of these factors were not available. Additionally, individual physiological stress responses to experienced events will vary and are influenced by a complex set of factors including genetics, personality, prior experience, social support and personal perception of these events, 49,50 which are also not considered here.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those without PPD confided about emotions such as a deep sadness after the experience of miscarriage or an uncomfortable health condition. It is reported that the pregnancy experience has both negative and positive elements, and that the more one shares about their anxiety and worries the more positive the experience (DiPietro et al, 2004). For mothers with the withdrawn style, having a baby could be conceived as an experience of not being in control.…”
Section: Discussionmentioning
confidence: 99%